Sorption Behaviour of Ibuprofen Using Activated Carbon Derived from Rose Geranium (Pelargonium graveolens L.) Leaves - Patience Mapule Thabede; Fanyana Mtunzi; Pardon Nyamukamba (Applied Sciences, 2023)
This research assessed the adsorption of a pharmaceutical compound, ibuprofen, using rose geranium (Pelargonium graveolens L.) leaves to prepare low-cost activated carbon through orthophosphoric acid (H3PO4) activation. The activated carbon from rose geranium leaves (AC-RGL) was characterized by TGA, SEM and FTIR. The results were compared with those from natural rose geranium leaves (Raw-RGL). The influence of chemical parameters for the uptake of ibuprofen on both adsorbents was evaluated through adsorption experiments. The results were subjected to adsorption models, kinetics models and thermodynamic studies to determine the distribution of ibuprofen in the solid and liquid phases. The results for both Raw-RGL and AC-RGL best fitted the Freundlich model, and the kinetic studies were shown to be pseudo-first order. The thermodynamic evaluation suggested exothermic and spontaneous process sorption for ibuprofen on both adsorbents. The maximum sorption capacities for AC-RGL and Raw-RGL were 113.76 and 74.12 mg/g, respectively. This work confirms that low-cost rose geranium leaves can be used as a potential adsorbent for the sorption of ibuprofen in solution.